Integration of traditional Sriwijaya music elements into progressive jazz: Innovation, aesthetics, and spirituality in a contemporary context - Mahameru, Erucakra; Cahyono, Agus; Suharto, Suharto; Batubara, Junita (Research Journal in Advanced Humanities, 2025)
This paper explores the process of integrating traditional Sriwijayan musical elements into contemporary progressive jazz compositions. It analyzes aspects of harmony, rhythm, and improvisation through innovative modal approaches such as the Lydian Universe and pedal tone shifting. By examining the impact on creativity, cultural appreciation, and spirituality, the study demonstrates that the fusion of traditional heritage with progressive jazz results in works that are relevant, original, and rich in aesthetic and philosophical depth. The research reinforces the importance of cross-cultural approaches in the development of modern music rooted in local traditions. Beyond musical exploration, this integration also represents an intercultural and intergenerational dialogue, where traditional elements—such as regional melodic motifs, rhythmic patterns characteristic of South Sumatra, and the spiritual atmosphere of Sriwijayan ritual music—are woven into the complex and open structures of jazz. This approach not only broadens musical horizons but also offers a contemplative space for listeners through a profound aesthetic and spiritual experience. The study employs music analysis and qualitative research methods to illustrate both the creative process and audience perceptions of this hybrid work. The findings suggest that this integration creates a new musical language that bridges past and present, local and global, intellect and emotion, into a cohesive and meaningful musical expression.